Definition of a metadata model for a multi–layered clinical practice guideline representation framework. (21st November 2012) - Kim, Matthew; Turechek, Zachary; Boxwala, Aziz; Hongsermeier, Tonya; Krall, Michael; Sonnenberg, Frank; Wright, Adam; Middleton, Blackford; Maviglia, Saverio
Representatives from a consortium of academic institutions, healthcare organisations, and commercial entities have collaborated to implement and evaluate a multi–layered representation framework targeted to promote the sharing and distribution of clinical practice guideline knowledge artefacts. Definition of a metadata model for knowledge artefacts submitted to a shared repository based on this framework proceeded through an iterative process that sought to strike a balance between the need to provide enough specification to allow for efficient indexing and retrieval and recognition of the potential burden imposed by excessive requirements.